مشکوۃ المصابیح کی کتاب الایمان میں واردمنتخب غریب الحدیث کاایک تحقیقی جائزہ : A Research Study of Selected Gharīb al-Hadīth Found in the Kitāb al-Imān of Mishkāt al-Masābīh - Mir Alam Khan,; Dr Muhammad Abdul Haq,; Prof Dr. Janas Khan, (Al Manhal Research Journal, 2025)
Explaining the general statements of the Qur’ān and clarifying its principles is beyond ordinary human understanding. Therefore, understanding its meanings requires the explanation and guidance of the Prophet Muhammad (peace be upon him), as the Qur’ān itself states that Allāh sent him to recite his verses, purify people, and teach them Qur’ān and contrivance. One main purpose of his mission was to make the Qur’ān’s teachings and meanings clear to the people. Mishkāt al-Masāb īh is an authentic collection of hadith compiled by Imām al-Khatīb al-Tabrīzī, who arranged selected narrations from various sources in a subjective order. It is important for both scholars and students and holds a special place in denī madāris. Many hadīths in this book explain matters of belief, morals, and faith, but some contain rare words unfamiliar to scholars and students. Without knowledge of Gharīb al-Hadīth (rare word in hadīth), a correct understanding of the hadīth is not possible. Conducting a lexical analysis of these terms, interpreting them in their context and explaining them in light of the statements of hadīth scholars is an academic necessity.